1980
DOI: 10.1029/rs015i004p00815
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and theoretical model of high‐resolution radar backscatter from the sea

Abstract: The temporal characteristics of radar backscatter from the sea depend on the pulse width for surface resolutions less than about 20 m. While low-resolution backscatter appears continuously noiselike, as the resolution is increased, the backscatter is punctuated by substantially quieter periods. This results in a noticeably 'spikey' characteristic. Measurements at 3 cm using several different pulse widths have been made near grazing incidence together with synchronized television views of the radar-illuminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 5 publications
0
54
0
Order By: Relevance
“…The pdf approach has been used, for instance, in microwave-based maritime surveillance and target detection [21], [22] but only recently with 0196-2892/$26.00 © 2011 IEEE optical data [23]. In addition, there is some previous work examining simultaneous signals in optical and microwave sensors [17], [24], [25]. However, the procedures for wave breaking identification have been fairly qualitative, and a high level of uncertainty persists.…”
Section: Introductionmentioning
confidence: 99%
“…The pdf approach has been used, for instance, in microwave-based maritime surveillance and target detection [21], [22] but only recently with 0196-2892/$26.00 © 2011 IEEE optical data [23]. In addition, there is some previous work examining simultaneous signals in optical and microwave sensors [17], [24], [25]. However, the procedures for wave breaking identification have been fairly qualitative, and a high level of uncertainty persists.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively few have attempted to relate backscatter specifically to measures of wave breaking. Lewis and Olin, [1980] used combined video and radar measurements to study shallow water breaking waves from the shore. Keller et al [1986] reported characteristic Doppler signatures of breaking events from CW scatterometers at moderate incidence.…”
Section: Introductionmentioning
confidence: 99%
“…According to the photographs and data taken in the field experiments [14,24], the single sharply crested unbroken wave can be approximately simulated with the dihedral wedge of finite length shown in Figure 1. Different from the infinite two-dimensional wedge in the previous literatures, the dihedral wedge is characterized by internal angle β, length d, width 2l and height h. Since the size of the wave crest is related to incidence microwave, d and 2l are presented in wavelength of incidence wave λ.…”
Section: Wedge-like Breaking Wavementioning
confidence: 99%
“…Although the sea surface scattering is successfully modeled based on the Bragg theory in small and moderate incidence angles [6][7][8][9][10][11][12][13], some discrepancies between the predictions and experiment observations still cannot be explained. The terminology "super events" refers to the special phenomenon observed from the measured sea clutters, which includes sea spikes [14], polarization independence [15], faster scatters [16] and expanded width of Doppler spectrum [17].…”
Section: Introductionmentioning
confidence: 99%